1990
DOI: 10.1080/00220671.1990.10885969
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Student Activities and Achievement: A Covariance Structural Analysis

Abstract: The place of student activities within the public educational system of this country remains an issue. Some proponents of educational reform argue that nonclassroom activities compete with academic learning for the student's time and attention. That argument implicitly assumes a causal relationship between youth activities and academic achievement. Using the High School and Beyond sophomore cohort data set, I examined that implied causal relationship between level of student participation in extracurricular/co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 13 publications
5
42
1
4
Order By: Relevance
“…Past research suggests that particular activities are associated with distinct academic outcomes (Broh, 2002;Camp, 1990;Fredricks & Eccles, 2005, 2006, 2008Hanks & Eckland, 1976), which could suggest that students with certain academic motives might be drawn to different activities. For example, students in profiles with more controlled forms of extrinsic motivation -i.e., high quantity and poor quality profilesmay choose to engage in activities that serve to strengthen their college applications.…”
Section: Extracurricular Activitiesmentioning
confidence: 99%
“…Past research suggests that particular activities are associated with distinct academic outcomes (Broh, 2002;Camp, 1990;Fredricks & Eccles, 2005, 2006, 2008Hanks & Eckland, 1976), which could suggest that students with certain academic motives might be drawn to different activities. For example, students in profiles with more controlled forms of extrinsic motivation -i.e., high quantity and poor quality profilesmay choose to engage in activities that serve to strengthen their college applications.…”
Section: Extracurricular Activitiesmentioning
confidence: 99%
“…Participation in school activities has also been associated with decreased risk of dropout and criminal arrest among teens classified as ''high risk'' (Mahoney 2000). Several studies have found an association between participation in school activities and higher standardized test scores, grades, and educational aspirations (Broh 2002;Camp 1990;Eccles et al 2003;Holland and Andre 1987;Marsh 1992;Spady 1970).…”
Section: Background the Relationship Between Activities And Educationmentioning
confidence: 99%
“…Several studies have found that television watching had no association with measures of student achievement, such as grades and tests in reading and math (Camp 1990;Gaddy 1986;Gortmaker et al 1990). …”
Section: Background the Relationship Between Activities And Educationmentioning
confidence: 99%
“…Indeed, in their summary of the relevant research, Holland and Andre (1987) and Otto (1982) lament the absence of longitudinal designs with selection controls and note that the strong positive results reported at that time may be due to the flawed use of cross-sectional designs and inadequate or nonexistent selection control methods. Cross-sectional studies published since these reviews continue to find positive relationships (Camp 1990;Gerber 1996;Lamborn et al 1992). Only Leuptow and Kayser (1973) found no relationship in a study of how participation in athletics is related to grades and educational aspirations.…”
mentioning
confidence: 99%